1996
DOI: 10.1002/jlb.59.5.663
|View full text |Cite
|
Sign up to set email alerts
|

PLA2 promotes fusion between PMN-specific granules and complex liposomes

Abstract: Neutrophil stimulation results in the activation of a variety of phospholipases, including phospholipase A2 (PLA2), which releases arachidonic acid from the 2 position of membrane phospholipids, leaving a lysophospholipid. Because arachidonic acid is known to be a potent fusogen in vitro, we examined the effect of metabolism by PLA2 on the fusion of complex liposomes (liposomes prepared with a phospholipid composition similar to that found in neutrophil plasma membrane). We observed that PLA2 augmented the fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 7 publications
2
21
0
Order By: Relevance
“…Nagao et al (1995) reported that the fusion of parotid SGs with PMs, as measured by a fluorescence-dequenching assay with octadecyl rhodamine B, was induced when the PM fraction was pre-treated with PLA2. Similar results were reported in neutrophils and chromaffin cells (Creutz, 1981;Karli et al, 1990;Blackwood et al, 1996). PLA2 was also shown to increase ZG and chromaffin granule lysis (Izumi et al, 1986;Gasser and Holda, 1994).…”
Section: The Role Of Lipids/fusinogens In Membranesupporting
confidence: 83%
See 1 more Smart Citation
“…Nagao et al (1995) reported that the fusion of parotid SGs with PMs, as measured by a fluorescence-dequenching assay with octadecyl rhodamine B, was induced when the PM fraction was pre-treated with PLA2. Similar results were reported in neutrophils and chromaffin cells (Creutz, 1981;Karli et al, 1990;Blackwood et al, 1996). PLA2 was also shown to increase ZG and chromaffin granule lysis (Izumi et al, 1986;Gasser and Holda, 1994).…”
Section: The Role Of Lipids/fusinogens In Membranesupporting
confidence: 83%
“…However, unlike AA, lysolipids appear to inhibit rather than promote fusion reactions (Chernomordik et al, 1993); these opposing effects have been shown to occur in the same cell type (Blackwood et al 1996). Because of these opposing effects, fusion mediated by lipid degradation products appears to be controversial in a physiologic context.…”
Section: The Role Of Lipids/fusinogens In Membranementioning
confidence: 99%
“…Another prominent aspect of PLA 1 reactions is that their products, lysophospholipids, generally have an inverted cone shape with a bulky polar head and a smaller fatty acid moiety and, therefore, generate positive membrane curvature (55,56). A number of studies have suggested that phospholipid hydrolysis induces morphological changes of membranes in vitro including fusion (57)(58)(59). However, it remains to be determined whether lipidmetabolizing enzymes have such roles in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of phosphatidic acid (40) and arachidonic acid (41) formation on membrane fusion events has been previously examined using exogenous phospholipases. The augmentation of phospholipid vesicle fusion by ceramide-1-phosphate was verified by the conversion of sphingomyelin to ceramide-1-phosphate with sphingomyelinase D. This augmentation was observed when as little as 0.5% (1% of the outer membrane leaflet) was ceramide-1-phosphate, suggesting that ceramide-1-phosphate formation potentially may play a positive regulatory role in PMN granuleplasma membrane fusion.…”
Section: Figmentioning
confidence: 99%